Evaluation of Faculty Readiness in Realizing the Entrepreneurial University Agenda: Case Study at the Faculty of Communication and Business Telkom University - Cristovao Moniz Joao; Astri Ghina (Global Writing Academica Researching & Publishing, 2023)
This study aims to measure the readiness of the Faculty of Communication and Business to support Telkom University to become an Entrepreneurial University. This research is descriptive in nature. The strategy used in this study is a case study. Based on the unit of analysis, this research was conducted in groups. Based on his involvement, this research is minimal. The research background used is non-contirived. Based on the implementation time, this research is cross-sectional. The object of this research is the Faculty of Economics and Business at Telkom University. The research subjects were the Head of the FKB Study Program, and the Dean of the FKB within Telkom University. The research implementation time is (September, 2020-January 2021). Data collection techniques used observation and interviews. The results showed that the Faculty of Communication and Business (FKB) has 3-4 courses that refer to Entrepreneurial, Entrepreneurial, StartupHup, and FKB has collaborated with external parties. All study programs at FKB have used a digital system, in terms of teaching, research and also community service (ABDIMAS), and in the Covid-19 Pandemic Era activities used an online system. The University provides funding to the faculty related to Entrepreneurial, and is consistent all study programs in FKB support their community members to take part in certified training programs on Entrepreneurial, and in the study programs themselves they often hold events for major student assignments, namely Urban Village. The study program always collaborates with external parties and on the preparation of the RPS. FKB holds an activity called EFBA where the lecturers become their supervisors, FKB students also often hold events so that their work results such as documentaries and others. And there is a mini market at FKB which can teach students directly about entrepreneurship. FKB has often participated in international and national level activities, FKB also has a program called Global Week where FKB invites guest lecturers from abroad. The Faculty of Communication and Business evaluates its programs at the end of each year.